Comparison of Knee Kinematics and Kinetics during Stair Ascent in Single-Radius and Multiradius Total Knee Arthroplasty - Sumner, Bonnie; McCamley, John D.; Jacofsky, David J.; Jacofsky, Marc C. (The Journal of Knee Surgery, 2019)
Traditionally total knee arthroplasty (TKA) design has been based on theories of the movement of the healthy knee joint. Currently, there are two competing theories on the flexion/extension axis of rotation of the knee with disparate radii of rotation, and thus differing movement patterns. The purpose of our study was to compare stair ascent kinematics and kinetics of single-radius (SR) and multiradius (MR) TKA subjects. We hypothesized that the knee kinematics and kinetics of SR TKA patients would more closely replicate healthy age matched controls during stair ascent than MR TKA patients, 1 year after TKA. Both patient groups had large improvements in biomechanical and clinical outcome measures following surgical intervention. However, the SR knee design performs closer to healthy controls than MR knees during stair ascent, supporting results that have been previously obtained for level walking. SR TKA subjects demonstrated reduced power production and sagittal moment compared with controls, albeit more than MR TKA subjects. This study demonstrates that patients who receive SR TKA have kinematics more closely aligned to normal patterns postoperatively than those who received an MR TKA. The power production and sagittal moment of the healthy controls most closely match previously published values of younger adults, SR TKA group most closely matches older adults, while the MR TKA group has lower power production and sagittal moments than either previously published age group. This strongly suggests that the biomechanical differences found in this study are evidence of functional deficiencies. Further research is needed to determine how these deficiencies progress with patient aging.
Keywords: total knee arthroplasty; stair ascent; knee axes of rotation; biomechanics